IMPLEMENTASI PROGRAM PEMBERDAYAAN MASYARAKAT (PRODAMAS) DALAM PERCEPATAN PEMBANGUNAN INFRASTRUKTUR (STUDI KASUS KELURAHAN NGRONGGO KOTA KEDIRI) - Mochammad 'Ainurroziqin; Susilo (Journal of Development Economic and Social Studies, 2024)
Prodamas is a breakthrough program of the Kediri City Government in accelerating regional development through direct community participation (empowerment). Prodamas seeks to realize the ability and independence of the community in infrastructure development, community economic improvement, and social community. This research uses descriptive research with a qualitative approach which is limited by the research focus, namely (1) Implementation of the Community Empowerment Program (Prodamas) in Ngronggo Village, City District, Kediri City seen from Merilee S. Grindle's theory which contains policy content and implementation context; (2) Supporting and inhibiting factors for the implementation of Prodamas. The data analysis method uses the Interactive model according to Miles, Huberman, and Saldana (2014) with four stages, namely data collection, data condensation, data presentation, and conclusion drawing. The results showed that the implementation of the Community Empowerment Program (Prodamas) in Ngronggo Village, City District, Kediri City based on policy content and implementation context is in accordance with the theory of Grindle (2017), it's just that the desired degree of change has not been measured, then the resources used need development and adjustment. Supporting factors for the Prodamas program come from human resources, teaching, budget, facilities and infrastructure, and academics. Meanwhile, the inhibiting factors come from bureaucratization which is still complicated, human resources, and the fact that the Prodamas program is still ineffective.